The Effectiveness of Prolonged-Release Melatonin in Primary Insomnia Patients with a Regular Sleep-Wake Cycle - Seockhoon Chung; Soyoung Youn; Boram Park; Suyeon Lee; Changnam Kim (Sleep Medicine Research, 2016)
Background and Objective Prolonged-release melatonin (PRM) might effectively increase patient satisfaction when administered to individuals older than 55 years old with primary insomnia who were not satisfied with their sleep even after their sleep-wake cycle schedule was set. We investigated patients’ satisfaction rate with PRM when they took it after their sleep-wake cycle was set. Methods Among 87 patients who were prescribed PRM at the sleep clinic, 44 patients with primary insomnia who complained of poor sleep quality even after adopting a set 7-hour sleep-wake schedule or taking sleeping pills 7 hours before wake-up time were selected their medical records were reviewed. We explored patients’ satisfaction rates with PRM after 3–4 weeks. Results Among the 35 subjects who completed follow-up, 23 (66%) reported an improvement in insomnia symptoms after taking PRM. Five subjects reported daytime sleepiness as treatment-emergent adverse events. Of the 25 subjects taking other sleeping pills at baseline and followed up, 11 (44%) reduced their sleeping pill dosage by at least 50%. Five subjects completely discontinued their previous sleeping pills after starting PRM. Conclusions We observed a high satisfaction rate with PRM when prescribed to patients with a regular sleep-wake cycle. We believe that the results of this study will help to optimize hypnotic prescription to insomnia patients.